2022
DOI: 10.5194/bg-19-2145-2022
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impacts of agricultural managements on soil carbon stocks, nitrogen loss, and crop production – a modelling study in eastern Africa

Abstract: Abstract. Improved agricultural management plays a vital role in protecting soils from degradation in eastern Africa. Changing practices such as reducing tillage, fertilizer use, or cover crops are expected to enhance soil organic carbon (SOC) storage, with climate change mitigation co-benefits, while increasing crop production. However, the quantification of cropland management effects on agricultural ecosystems remains inadequate in this region. Here, we explored seven management practices and their potentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 105 publications
1
3
0
Order By: Relevance
“…Ahrens et al, 2014). Nevertheless, our results of high SOM turnover in Kenya are in line with the results of two recent studies, which also found that the default parameterizations of the DayCent (Nyawira et al, 2021) and the LPJGUESS model (Ma et al, 2022) underestimated the loss of SOC in two other long-term experiments in Kenya. In our study, the low Sobol total sensitivity indices of the maize productivity parameters for the SOC stocks suggest a limited importance of root input in the soil system for the storage of SOC.…”
Section: Bayesian Calibration Suggests That Soc Is Lost At Higher Rat...supporting
confidence: 92%
See 1 more Smart Citation
“…Ahrens et al, 2014). Nevertheless, our results of high SOM turnover in Kenya are in line with the results of two recent studies, which also found that the default parameterizations of the DayCent (Nyawira et al, 2021) and the LPJGUESS model (Ma et al, 2022) underestimated the loss of SOC in two other long-term experiments in Kenya. In our study, the low Sobol total sensitivity indices of the maize productivity parameters for the SOC stocks suggest a limited importance of root input in the soil system for the storage of SOC.…”
Section: Bayesian Calibration Suggests That Soc Is Lost At Higher Rat...supporting
confidence: 92%
“…Robust predictions of crop yields and changes in SOC stocks, as achieved by our cross-validation, are an important basis for potential future upscaling exercises of crop yield and SOC model predictions to national scales. While many model calibration exercises often display an overly optimistic picture of the capacity of models to represent SOC dynamics, by displaying how well the models represent absolute levels of SOC (e.g., in Nyawira et al, 2021;Ma et al, 2022;Levavasseur et al, 2021), the changes in SOC since the start of an experiment, shown in this study, are much more robust evaluation. Since models are typically parameterized to fit the observed SOC stock at the start of the experiment, absolute SOC will always closely resemble measurements, with the possible exception of experiments that run for many decades.…”
Section: Robustness Of the Bayesian Calibration Shown By Cross Evalua...mentioning
confidence: 98%
“…They store around 34% of the terrestrial carbon stock and provide a variety of ecosystem services including forage production, plant diversity conservation, and climate regulation 39 . Croplands are widespread globally, and most agricultural practices reduce soil carbon content 38 , 40 , thus organic fertilizers have the potential to increase SOC under agricultural management practices. We hypothesized that: (1) organic fertilization would increase aboveground biomass more than inorganic fertilization in grasslands, (2) if increased biomass production intensified competition for light, or fertilization reduced belowground niche partitioning, organic fertilization would also cause a decline in plant diversity in grasslands, and (3) if nitrogen detriment (e.g., acidification) was the main mechanism, organic fertilization would not cause plant diversity loss in grasslands.…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to site‐level modeling studies, an assessment of the impacts of CCs across regions or globally is still lacking, as a result of inadequate management information (e.g., spatial pattern of cover crop types) and missing or incomplete cover cropping representation in models (Porwollik et al., 2022). For large‐scale C‐N cycle modeling assessments, alternative agricultural practices so far have been evaluated through stylized model setups with homogenous assumptions of management intensities (Jang et al., 2021; Lutz et al., 2020; Ma, Rabin, et al., 2022; Olin, Lindeskog, et al., 2015). For example, Olin, Lindeskog, et al.…”
Section: Introductionmentioning
confidence: 99%